Strengthening Religious Moderation through Islamic Religious Education Learning: Integrative Planning, Dialogical Instruction, and Continuous Evaluation - Ahmad Burhanuddin Haris; Ach. Sayyi; Ismail Ismail (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
The strengthening of religious moderation in elementary education has become an important issue due to the tendency of Islamic Religious Education learning to emphasize cognitive aspects rather than the development of tolerant and balanced religious attitudes. This study aims to analyze how religious moderation is strengthened through Islamic Religious Education learning, focusing on integrative planning, dialogical instruction, and continuous evaluation. This research used a qualitative case study conducted at an Islamic elementary school selected purposively. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model with triangulation for validity. The findings show that religious moderation is strengthened through the integration of moderation values in lesson planning, dialogical and contextual learning practices, and continuous evaluation of students’ attitudes. These stages form a consistent learning system that supports the development of moderate, tolerant, and responsible religious character at the elementary level.